"Le Martyre de Saint Sebastien" di Gabriele D’Annunzio: Una lettura queer - Clemente, Francis (Mimesis Journal, 2021)
The present article aims to deliver a queer reading of Gabriele D’Annuzio’s Le Martyre de Saint Sebastien (1911). By openly designating the saint as a subject of homoerotic desires and a languid and androgynous being interpreted by an androgynous dancer, D’Annunzio ends up questioning and subverting gender categories pertaining to the hegemonic order, creating a disruptive play based on gender ambiguity, the undermining of normative identities and orientations, and the will to arouse bewilderment as a result of these ambiguity and undermining. The article explores the queer charge of D’Annunzio’s drama focusing on its composition, representation, and text.